2017
DOI: 10.1021/acs.langmuir.7b03193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solid Fraction on Droplet Wetting and Vapor Condensation: A Molecular Dynamic Simulation Study

Abstract: Recently, numerous studies focused on the wetting process of droplets on various surfaces at a microscale level. However, there are a limited number of studies about the mechanism of condensation on patterned surfaces. The present study performed the dynamic wetting behavior of water droplets and condensation process of water molecules on substrates with different pillar structure parameters, through molecular dynamic simulation. The dynamic wetting results indicated that droplets exhibit Cassie state, PW stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 46 publications
(47 reference statements)
3
50
0
Order By: Relevance
“…Numerous studies have been performed on the behavior of vapor condensation to understand its mechanism under various conditions [8,9,10,11]. Condensation which occurs on a surface is more frequent than that found directly in the vapor phase because of the wide existence of solid substrate that can be seen as the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed on the behavior of vapor condensation to understand its mechanism under various conditions [8,9,10,11]. Condensation which occurs on a surface is more frequent than that found directly in the vapor phase because of the wide existence of solid substrate that can be seen as the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Various theoretical and semiempirical models have been proposed to describe the relationship between surface structure and nucleation, for example, interfacial free energy analysis and cluster theory [16,17,19,74]. To obtain more detailed information on the droplet nucleation in micro/nanostructures, many numerical modeling methods have been developed such as the Gibbs free energy analyses, finite element method, lattice Boltzmann method, lattice density functional method, and molecular dynamics (MD) simulations [13,18,[75][76][77][78][79][80].…”
Section: Nucleation and Droplet Size Distributionmentioning
confidence: 99%
“…They found that the presence of nanostructures reduced the surface thermal resistance and promoted the increase of the evaporation rate of ultrathin liquid film. Gao [ 16 ] quantitatively recorded the condensation process of water vapor on flat and pillar-structured surfaces. Further studies regarding the effect of the wettability on condensation and the phenomenon of heat transfer are needed.…”
Section: Introductionmentioning
confidence: 99%